(untitled) (Journal of Philosophy Culture and Political Science, 2016)
In domestic musicology modern musical art of Uygurs wasn’t object of close attention of art critics. There are not studied many questions, in particular, connected with identification of sources and prerequisites of formation of performing and composer creativity, stages of formation and development of the Uigur art of a platform, role of modern leading Uigur performers and composers, definition of a phenomenon of the Uigur vocal variety culture from the point of view of its national originality, disclosure of interference and interpenetration West European academic traditions and national Uigur folklore. Article is devoted to research of genesis and development of the Uigur variety music in Kazakhstan. Process of formation of the Uigur variety art was followed by combination of a number of factors of an ethnic, social, cultural order. As a result of interaction of various traditions – West European, Russian and east, belonging to culture and activity of the people, emergence of professional national Uigur variety art became possible. In article the problem of functioning of modern Uigur music, its existing on a platform of Kazakhstan rises, creativity of Yashlyk group, as one of founders of the direction of vocal instrumental music is considered.